The Methods Promoting the Mental Health of the Kindergarten Child in Light of the War on Syria - A field study on the Sample of kindergarten Care takers in Lattakia City (Journal of Hama University, 2025)
The research aimed to identify the degree of kindergarten teachers’ contribution to strengthening children’s mental health in light of the Syrian crisis represented by (positive thinking, self-confidence, social competence, self-efficacy, and emotional control) among kindergarten children of the third age group (5-6) years in In light of the Syrian crisis, the descriptive approach was adopted, and to achieve the research goal, a questionnaire consisting of (78) items was used, and it was applied to a sample consisting of (184) kindergarten educators in Latakia city.The most important findings of the research is that the degree of kindergarten teachers’ contribution to strengthening children’s mental health in light of the Syrian crisis was moderate, and the field of enhancing social competence ranked first, followed in second and third place by enhancing the fields of self-confidence and emotional control, then came in second and third place. Fourth is the area of enhancing positive thinking, and in fifth and final place is the area of enhancing self-efficacy.In light of the findings of the research, the research made several recommendations, the most important of which are: Preparing courses to raise the awareness of kindergarten educators of the importance of promoting the sound mental health of children, and necessity of appointing psychologists and counselors in each kindergarten, also Selecting kindergarten nannies according to special criteria in terms of qualification and experience in dealing with children.
Keywords: Mental Health, Kindergarten Child, Kindergarten Care Takers, War on Syria